Management of synchronous arterial occlusions using intra-arterial thrombolysis. - Barr, H. (Royal College of Surgeons of England, 1992)
Three patients presented with multiple acute arterial occlusions in separate limb vessels. The diagnosis was confirmed by angiography. Each patient was successfully treated by simultaneous infusion of low-dose intra-arterial streptokinase into each occlusion. All of the patients were improved clinically and in two patients completely normal pressure indices were restored.